Eco-Friendly Tri-Sodium Citrate as Corrosion Inhibitor for Mild Steel in Synthetic Cooling Water System - Touir,; A. Koulou,; M. Chahboune,; Y. El Kacimi ,; H. Larhzil, (Journal of Basic & Applied Sciences, 2020)
The influence of an ecofriendly tri-sodium citrate (TSC) on the inhibition of mild steel corrosion in synthetic cooling water was studied by using potentiodynamic polarization (PP), and electrochemical impedance spectroscopy (EIS) measurements. The state of mild steel surface was characterized by scanning microscopy electron (SEM) analysis. It is found that TSC acts as an anodic type inhibitor where its inhibition increases with concentration to reach a maximum of 89 % at 10-3 M. Indeed, the EIS plots revealed that TSC increases the polarization resistance of mild steel confirming the current-potential measurement and indicated that the inhibition efficiency of TSC increase with immersion time until 24 h of immersion. SEM investigation demonstrated that the inhibition of mild steel in corrosive/TSC solution was realized by the TSC molecules adsorption onto mild steel to prevent the dissolution process by blocking the active sites on its surface. Thus, it is shown that the TSC obey to the Langmuir isotherm and it is adsorbed via both physical and chemical adsorption which can explain by potential of zero charge (PZC) technique.